Freqüência de anticorpos Anti-Rickettsia spp em cães da cidade de Belo Horizonte, Minas Gerais, Brasil, 2005. - Manoel Eduardo da Silva (2007)
Brazilian Spotted Fever (BSF), caused by Rickettsia rickettsii, is endemic and highly lethal for humans in some areas of Southeastern Brazil. However, in the city of Belo Horizonte, capital of the state of Minas Gerais, BSF is not endemic. The present study aimed to evaluate rickettsial infection among the canine population of Belo Horizonte. For this purpose, 453 dog sera, representing the entire canine population of the city, were tested against five rickettsial antiges (Rickettsia rickettsii, Rickettsia parkeri, Rickettsia amblyommii, Rickettsia felis and Rickettsia bellii) using the indirect immunofluorescence assay (IFA). Sera were considered positive if reacted with titers > 64. Only 3 out of 453 sera were reactive to Rickettsia spp, giving an overall prevalence of 0.66% of rickettsial infection among the canine population of Belo Horizonte. At least one of these 3 sera was considered homologous to Rickettsia rickettsii because it displayed a titer to this species four-fold higher than those elicited for the remaining Rickettsia species. We conclude that BSF is not endemic in Belo Horizonte, although new serosurveys must be conducted to verify the endemic status of this area in the near future.